The Relationship between Daily X (Twitter) English Usage and the Vocabulary Mastery of Eleventh Grade Students at SMAN 1 Samarinda - A.K. Amarullah, S.S., M.Pd; Fathya Azzahra; Dr. Phil. Maria T. Ping, M.Sc (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2025)
The present study was aimed to investigate whether there is a relationship between daily X (Twitter) English usage and vocabulary mastery. The objective was to find out (1) the intensity of students’ daily X (Twitter) English usage; (2) the students’ vocabulary mastery; (3) the relationship between the intensity of students’ daily X (Twitter) English use and students’ vocabulary mastery. The design of the study was correlational quantitative research. The population was eleventh grade students, and the sample was 141 students who were using X (Twitter). The instruments of this study were a questionnaire and a multiple choice test. The data were analyzed by using Spearman Rank on SPSS 23. The finding of this study was (1) the intensity of students’ daily X (Twitter) English use was categorized as low, with the mean score 57.68; (2) the vocabulary mastery of students was categorized as excellent, with the mean score 81.6140; (3) the correlation correlation coefficient value was 0.101. In addition, p-value was 0.231 (>0.05). It indicated that there was no significant relationship between daily X (Twitter) English use and the vocabulary mastery of eleventh grade students at SMAN 1 Samarinda. The results of this study implied that students did not consider X (Twitter) as a vocabulary learning tool. In addition, students may have an excellent vocabulary without using X (Twitter). This study can be useful for future researchers as they can further investigate what are the factors of students’ English vocabulary mastery. Furthermore, they can also conduct an experimental study using the same subject and objective of the current study.